The determinants of housing price in Malaysia / Nurul Habibah Imanuddin Zangki - Imanuddin Zangki, Nurul Habibah (Faculty of Business Management, 2015)
House is one of the human basic physiological needs. In this modest era, house comes in a form of house and it is the most important component of the socio-economy sector. Reviewing housing price in Malaysia, the prices have appreciated dramatically whether in major cities or smaller towns and depending on specific location. There are many internal and external factors that may affect the changes of housing prices in Malaysia. The purpose of this study is to find main factors that affecting the housing price in Malaysia. In this study, it focused on four independent variables. Which are Gross Domestic Product, Inflation Rate and Interest Rate. Total of 36 observations each variable from January 2006 until December 2014 quarterly basis has been used in this research. The variability of the price of housing may impact the economy growth of the country in terms of trade balance.